Diagnostic and Prognostic Roles of Serum Interleukin-6 Levels in Patients with Uveitis. (17th February 2022) - Maleki, Arash; Gomez, Sebastian; Asgari, Soheila; Bosenberg, Zoe; Manhapra, Ambika; Walsh, Marisa; Weng, Angelina; Tsang, Catherine; He, Celestine; Anesi, Stephen Damien; Foster, C. Stephen
ABSTRACT: Purpose: To examine the diagnostic and prognostic roles of serum interleukin-6 levels in patients with uveitis. Methods: This was a retrospective observational case series. Demographic and clinical characteristics were compared between Group One (sixty patients) with normal serum IL-6 levels and Group Two (twenty patients) with high serum interleukin-6 levels. Results: Mean IL-6 level was 1.77 ± 0.97 pg/ml and 10.2 ± 9.7 pg/ml in Group One and Group Two respectively. Age, presence of systemic disease, and mean number of flare-ups were statistically significant ( p = .015, p = .000, p = .03, respectively). Multivariate analysis was performed on variables that were statistically significant in univariate analysis and showed that three variables had significant correlation with IL-6 levels in both groups: systemic disease (OR = 10.83, p < .001), Age (OR = 0.95, p = .03) and number of flare-ups (OR = 2.9, p = .02). Conclusion: Serum IL-6 levels can provide diagnostic and prognostic information in regard to the course of disease and its treatment.